Colonized patients by Candida auris: Third and largest outbreak in Brazil and impact of biofilm formation - de Melo, Camylla Carvalho; de Sousa, Bruna Rodrigues; da Costa, Gisela Lara; Oliveira, Manoel Marques Evangelista; de Lima-Neto, Reginaldo Gonçalves (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To describe the clinical–epidemiological features of patients colonized by Candida auris in the largest outbreak in Brazil and to show the biofilm formation capacity of yeast strains. Methods Clinical yeasts suspected of C. auris isolated from urine and surveillance samples were seeded on chromogenic media at 30°C and Sabouraud agar at 42°C. matrix-assisted laser desorption/ionization–time of flight mass spectometry was used for reliable identification. After proteomic confirmation, the genomic approach and culture on Chromagar Candida Plus media were carried out. Biofilm formation was investigated based on metabolic activity, and the clinical–epidemiological profile of patients was described. Results A total of 11 C. auris clinical yeasts from nine patients were identified between the end of December 2021 and March 2022. Two clinical yeasts were isolates from urine and nine clinical yeasts were isolates from axillary and inguinal surveillance swabs. No case is related to previous Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, all the yeasts showed a high ability of biofilm formation. Conclusion C. auris requires great vigilance as its high capacity to colonize and form biofilms contributes to its dissemination. The rapid and precise identification of this species is essential for the management, control, and prevention of infections.